Scream VI [videorecording (DVD)] - Vanderbilt, James; Busick, Guy, 1975-; Barrera, Melissa, 1990-; Brown, Jasmin Savoy, 1994-; Champion, Jack, 2004-; Czerny, Henry; Gooding, Mason, 1996-; Liberato, Liana, 1995-; Mulroney, Dermot; Nekoda, Devyn, 2000-; Ortega, Jenna; Revolori, Tony, 1996-; et al. (Paramount Home Entertainment, 2023)
In the sixth installment, the survivors of the Ghostface killings leave Woodsboro behind and start afresh in New York City.